(untitled) (The Pakistan Development Review, 2016)
The existence of large and persistent current account deficit is always viewed with great concerns, as it usually leads an economy to a state of insolvency due to building up excessive net foreign debt. As the current account deficit is a persistent feature of Pakistan’s economy, therefore, it becomes essential to empirically investigate, whether this deficit is sustainable or not. To this end, the present study has applied two alternative approaches, namely, the intertemporal approach to the current account and the intertemporal solvency approach, in order to get more convincing evidence on the sustainability issue in Pakistan using the time series data over the period 1960 to 2012. From the perspective of both the approaches, Pakistan’s current account deficit is on a sustainable path and the macroeconomic policies of the country remained effective in securing it from any external sector crisis. JEL Classification: C32, F32, F41 Keywords: Current Account Deficit, Intertemporal Budget Constraint, VAR Model, Cointegration